Problem-based learning to establish social presence: A mixed method investigation in different modes of classroom management practices - Murtafi'ah, Banatul; Ardini, Anandayu Suri (UPT Bahasa Universitas Tanjungpura, 2025)
Post-pandemic learning has led schools in Indonesia to conduct a teaching transition from online to hybrid to offline learning. This uncertain situation has forced pre-service English teachers (PSETs), to be able to adapt to any mode of classrooms. Moreover, PSETs must have the social presence ability to manage online, offline, or hybrid classrooms. However, few studies examined how problem-based learning (PBL) can facilitate the establishment of social presence in classroom management practices among PSETs. This study investigates how PBL can establish PSETs